EKSTRAKSI TANIN DARI DAUN JAMBU BIJI SEBAGAI BAHAN PENYAMAK NABATI - Sumarni -; Helen Firda Tomanda; Yunita Safitri A. Lakuba (PROSIDING SNAST, 2018)
In Indonesia, there are still many tannery factories that use tanneries which have the potentialas environmental pollutant. One type of tanneries used is chrome (Cr). The use of this material produces very high levels of waste. Therefore, the leather tanning producers switch to using more environmentally friendly materials, such astannin. Tannin can be used as natural tanneries that are more environmentally friendly. Generally, tannin is found in plants such as leaves, fruit peels, stems, and bark. One of materials that has high tannin content is guava leaves. This research aims to determine the method ofextracting tannin from guava leaves with extraction process. The extraction process was carried out using 40 grams of red guava leaves with 96 mL ethanol solvent as much as 100 mL and a stirring speed of 250 rpm. This processes were carried out using variation in extraction time, extraction temperature, solvent volume, and stirring speed. The analysis includes analysis of water content, analysis of tannin content in raw materials, and analysis of extracted tannin. From the research that has been done, obtained the results of tannin content of raw materials were 4.42 grams or 10.5%. The best process conditions were obtained at 150 minutes, temperature of 65oC, and stirring speed of 400 rpm with the extracted tannin percentage of 85.44% or weighing 3.78 grams.